BIOLOGIA E ECOLOGIA DE HIMENÓPTERAS QUE NIDIFICAM EM CAVIDADES PREEXISTENTES EM GUARAPUAVA, PR - DEUS, JEAN PABLO ALVES DE (2020)
This dissertation was divided into two chapters involving two different levels of study, one involving more macroscopic aspects with the ecology of communities and the other involving biological aspects of a little-known species. Thus, the first chapter was a study of the ecology of the community of solitary wasps and bees and their parasites, measuring the effect of the type of habitat on the structure of these communities and their interactions. In this study, the composition and abundance of species, but not the richness and interactions of hosts and parasitoids, were altered in the three types of habitats. A forest is home to a higher concentration and distinct species composition compared to other habitats. The turnover of both groups of insects was greater among forests and other habitats in the field and in the floodplain. In conclusion, environmental heterogeneity plays a central role in maintaining high biodiversity in the Atlantic Forest. The second chapter, on the other hand, focused on the natural history of a species of solitary wasp Pisoxylon amenkei, which is considered a rare species within the Araucaria Forest. Pisoxylon amenkei nested only in fragments of forest, during the summer and autumn. It is a multivoltine species, which remains in diapause in the pre-pulp phase in winter and spring. The P. amenkei nests found architecture similar to the nests of Pisoxylon xanthosoma and species of Trypoxylon. In addition, the sex ratio of P. amenkei was 1: 1, or it may be linked to the same cost of producing males and females. We can conclude that P. amenkei nest only some areas of the forest and the results of this study show some similarities and differences between Pisoxylon and Trypoxylon. Therefore, studies with an emphasis on the phylogeny of the group and the use of molecular molecules are more necessary to clarify this issue. Regardless, here we show unprecedented data on the biology of P. amenkei species and that the preservation of forest fragments can be a good strategy for the conservation of rare species, such as P. amenkei. Results found in studies like these can be of great ecological and economic interest, in addition to showing important aspects that influence these communities in natural habitats, they increase our knowledge about important species that provide ecosystem services that are essential not only for natural environments as well as environments anthropized like agriculture.